2009
DOI: 10.1094/mpmi-22-8-1011
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Citrus Huanglongbing Bacterium, ‘CandidatusLiberibacter asiaticus’ Obtained Through Metagenomics

Abstract: Citrus huanglongbing is the most destructive disease of citrus worldwide. It is spread by citrus psyllids and is associated with a low-titer, phloem-limited infection by any of three uncultured species of alpha-Proteobacteria, 'Candidatus Liberibacter asiaticus', 'Ca. L. americanus', and 'Ca. L. africanus'. A complete circular 'Ca. L. asiaticus' genome has been obtained by metagenomics, using the DNA extracted from a single 'Ca. L. asiaticus'-infected psyllid. The 1.23-Mb genome has an average 36.5% GC content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
538
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(551 citation statements)
references
References 66 publications
7
538
2
4
Order By: Relevance
“…These variations are noticeable from nutritional disorders caused by Ca. Liberibacter spp., especially in the form of deficiencies and prevention of translocation in phloem (Duan et al, 2009). Giles (2011) reports on successful leaf application of nutrients to promote longevity and better citrus production, when it is infected with HLB (no replicated data available).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations are noticeable from nutritional disorders caused by Ca. Liberibacter spp., especially in the form of deficiencies and prevention of translocation in phloem (Duan et al, 2009). Giles (2011) reports on successful leaf application of nutrients to promote longevity and better citrus production, when it is infected with HLB (no replicated data available).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expressive responses on nutritional process, observed in infected plants asymptomatic and symptomatic, are attributed to the increase in volumes of N, Ca, Mg, S, B, Fe, Mn, Mo and Zn applied through leaf treatment, mainly by plants chlorotic due to the obstruction of sieve pores and impaired translocation of nutrients and photosynthates due to the severity of disease (Cardinali et al, 2012.). According to reports by Duan et al (2009), Ca. Liberibacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Besides its ATP synthase CLas also encodes ATP/ADP translocase, which means that CLas can synthesize its own ATP or utilize it directly from its host. 23 To test this hypothesis, Vahling et al (2010) expressed the ATP translocase, nucleotide transport protein (NttA) gene encoded by CLas, in Escherichia coli.…”
Section: Atp and The Growth Of Clasmentioning
confidence: 99%
“…For example, the sequencing of the CLas genome showed that CLas cannot synthesize tyrosine, tryptophan, valine, leucine, and isoleucine from their metabolic intermediates. 23 Consequently, CLas should obtain these essential amino acids from its hosts. The chemical analysis of the citrus phloem sap showed that all of these essential amino acids exist in the citrus phloem sap.…”
Section: Introductionmentioning
confidence: 99%